State ownership and risk-taking behavior: An empirical approach to get better profitability, investment, and trading strategies for listed corporates in Vietnam - Nguyen Tran Thai Ha; Massoud Moslehpour; Thi Thuy Van Vo; Wing-Keung Wong (Economies, 2020)
Corporate risk-taking behavior and investment is a crucial factor in order to seek higher profits and a better trading strategy. Competitive advantage and innovation, while maintaining profitability and state ownership, are considered as crucial resources. Furthermore, it is essential to connect the short-term and long-term business and investment objectives plus stakeholder's expectations to corporate sustainability and development. This connection is especially important in the context of transforming economies and getting better trading strategies. This study estimates the relationship between state ownership, profitability, corporate risk-taking behavior, and investment in Vietnam by using Generalized Method of Moments (GMM) methods. Using the data of 501 listed non-financial corporates during the period 2007-2015 from Ho Chi Minh City and Hanoi Stock Exchanges, we find that profitability is determined as a factor to reduce corporate risk-taking acceptance caused by the chances of entrenchment. Meanwhile, the impact of state ownership on the risk appetite of corporate has a non-linear effect. In particular, state ownership reduces corporate risk-taking behavior and investment but yet increases the risk-taking behavior and investment when the state ownership rate exceeds a threshold. One the one hand, this implies that the low level of state ownership not only prevents risk-taking behavior and investment but also results in more severe agency problems, causing unsustainability due to the imbalance of interests among various stakeholders. On the other hand, a dominant role of state ownership concentration causes a boost in corporate risk-taking decision-making in investment and trading strategy, leveraging the connection of significant external resources to deal with uncertain problems. The study contributes to existing theories of corporate governance in the context of a socialist-oriented market.
Keywords: G30; G38; 330; market efficiency; nonlinearity; investment; Vietnam; GMM; risk-taking behavior; state ownership; trading strategy